The cause-and-effect relationships between the real estate market and the stock market in Poland - Nowak, Krzysztof (Zależności przyczynowo-skutkowe między rynkiem nieruchomości oraz rynkiem giełdowym w Polsce, 2020)
The real estate market and the stock market are two elements of the financial market. The objective of the article is to verify if there can be established the cause-and-effect relationships between these two markets in Poland. In order to realise that goal the author verified if quotations of the WIG Real Estate index are affected by the mean transaction price of new apartments in 10 voivodeship cities, the number of apartments with the official permit to inhabit, as well as the value and number of new mortgage loans. The relationships between the WIG Real Estate and two main stock indexes quoted on the Warsaw Stock Exchange were also examined. Three Vector Auto-Regression models were formulated, and a Granger causality test was conducted. The study revealed that only lags of the number of apartments put into use did not affect the WIG Real Estate. Moreover, the time series of the mean transaction price of new apartments impacts most on the WIG Real Estate
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 118-132